RETRACTED: 20-HETE Inhibition by HET0016 Decreases the Blood–Brain Barrier Permeability and Brain Edema After Traumatic Brain Injury - Lu, Liyan; Wang, Mingliang; Wei, Xiaoer; Li, Wenbin (Frontiers in Aging Neuroscience, 2018)
Recent studies have implicated 20-HETE as a vasoconstrictive mediator in trauma, the purpose of this study was to determine whether administration of HET0016, the 20-HETE inhibitor, could protect neurons from trauma and the effect of HET0016 on the blood–brain barrier (BBB) and brain edema in experimental traumatic brain injury (TBI). Rat models with TBI were established. Brain edema was measured according to the wet and dry weight method at 3, 24, and 72 h after injury. The BBB permeability was quantified by dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). Superoxide production, the activity of superoxide dismutase (SOD) and total antioxidative capability (T-AOC) in traumatic brain tissues were also measured. Western blot analysis was used to analyze the expression of the occludin, ZO-1, Matrix metalloproteinase-9 (MMP-9), and c-Jun N-terminal protein kinase (JNK) pathways. At 24 and 72 h after administration of HET0016 following TBI, the BBB permeability and brain edema decreased. The decrease in superoxide production and the increase in the activity of SOD and T-AOC were measured in this study. Western blot analysis showed that the expression of MMP-9 and JNK pathways was suppressed, but the expression of ZO-1 and occludin was increased. These results suggest that the administration of HET0016 could protect the BBB function and decrease brain edema after experimental traumatic injury by suppressing the expression of MMP-9 and activating the expression of tight junction proteins via suppressing the JNK pathway and oxidative stress.